BIO-CHEM KIT: understanding biogeochemical cycles / Nurul Hidayana Mohd Noor ... [et al.] - Mohd Noor, Nurul Hidayana; Hamid@Hussain, Shawal Sahid; Yaacob, Mahazril 'Aini; Hashim, Mohd Hafiz Hazwan (2021)
One way of handling significant amounts of information is through visuals. Infographics can transfer knowledge about a topic faster and more effectively than pure text. BIO-CHEM KIT is a set that uses QR codes and online quizzes in learning activities, consisting of quick and important elements on the principles of the ecology field for students, lecturers, and practitioners. The main purpose of this graphic visual is to enhance learners' basic knowledge of important biogeochemical cycles and. The innovation ideas also serve as teaching and learning materials for lecturers and students. It also benefits the practitioners in environmental administration, which use can be used as a quick reference guide. Furthermore, this innovative idea is hoped to make teaching and learning environmental courses easy, memorising, and faster especially during the online distance learning in the era of the Covid-19 pandemic.